Założenia przebudowy systemu publicznej radiofonii i telewizji w projekcie ustawy o zadaniach publicznych w dziedzinie usług medialnych zespołu ekspertów Ministra Kultury i Dziedzictwa Narodowego z 30 listopada 2008 r. - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The objective of the study is to present the solutions proposed in the amendment to the law on radio and television concerning public media. An analysis is made of the bill on the public tasks of media services, drafted by a team of experts appointed by the Minister of Culture and National Heritage and headed by Professor Tadeusz Kowalski. The team also comprised Prof. Stanisław Jędrzejewski, Att. Robert Kroplewski, Att. Tomasz Kapliński, Renata Czarnkowska (acting as secretary) and the author of this paper. The team held numerous meetings in Warsaw from June to November 30, 2008 when the final result of the work, namely the bill, was announced and presented at a press conference.